2015
DOI: 10.1111/bph.13332
|View full text |Cite
|
Sign up to set email alerts
|

Contractile function assessment by intraventricular balloon alters the ability of regional ischaemia to evoke ventricular fibrillation

Abstract: BACKGROUND AND PURPOSEIn drug research using the rat Langendorff heart preparation, it is possible to study left ventricular (LV) contractility using an intraventricular balloon (IVB), and arrhythmogenesis during coronary ligation-induced regional ischaemia. Assessing both concurrently would halve animal requirements. We aimed to test the validity of this approach. EXPERIMENTAL APPROACHThe electrocardiogram (ECG) and LV function (IVB) were recorded during regional ischaemia of different extents in a randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Male Wistar rats (Harlan UK; 220–410 g) were anaesthetized by i.p. injection of a lethal dose of sodium pentobarbitone (170 mg·kg −1 ) and co‐administered sodium heparin (160 IU·kg −1 ) (Wilder et al, ). A surgical level of anaesthesia was determined by the absence of pedal and corneal reflexes, prior to cardiac excision and exsanguination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Male Wistar rats (Harlan UK; 220–410 g) were anaesthetized by i.p. injection of a lethal dose of sodium pentobarbitone (170 mg·kg −1 ) and co‐administered sodium heparin (160 IU·kg −1 ) (Wilder et al, ). A surgical level of anaesthesia was determined by the absence of pedal and corneal reflexes, prior to cardiac excision and exsanguination.…”
Section: Methodsmentioning
confidence: 99%
“…An arrhythmia score was assigned to each heart for ischaemia and (separately) for reperfusion in order to permit parametric statistical analysis. All these assessments were as described previously (Wilder et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The difference in infarct size between these two groups was found in the endocard and may represent a balloon-induced injury. In a recent study in rats, no difference was found in infarct size between a balloon group and a non-balloon group, but interestingly, they found an increase in lactate release after removal of the balloon compared to no balloon, indicating a subendocardial hypoxia with the balloon present (Wilder et al 2016). Another interesting finding was a balloon-induced alteration in post-ischaemic ability for ventricular fibrillation (Wilder et al 2016).…”
Section: The Presence Of the Balloon Increases Infarct Sizementioning
confidence: 97%
“…In some groups (see below) a fluid-filled balloon-tipped pressure catheter was inserted into the left ventricle via the left atrium to measure heart rate (HR) and ventricular pressures using the Powerlab system (ADInstruments, NSW, Australia). Intraventricular balloon for mice are not commercially available and was made in the lab using non-compressive ultrathin plastic (Wilder et al, 2016).…”
Section: Langendorff Perfusionmentioning
confidence: 99%
See 1 more Smart Citation